Rancang Bangun Alat Keamanan Pada Shoesbox Menggunakan Sensor Passive Infrared Receiver (PIR) Berbasis Arduino dan IoT - Wijaya, Zidan Rizky; Budiarso, Zuly (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Theft of valuables such as high-priced branded shoes is a crime that often occurs. As cases of theft increase, this research aims to reduce the number of theft incidents, especially those targeting valuable items such as shoes stored in shoe boxes. This research proposes the development of a security tool for shoe boxes equipped with a Passive Infrared (PIR) sensor to detect movement, Nodemcu esp8266 as the brain of the system, and the Blynk application as an Internet of Things (IoT) platform. This research will take the form of a Shoebox security tool that can provide shoesbox security notifications. This tool is designed to increase the security of shoe boxes, helping to effectively reduce the incidence of theft.